Studi Literatur: Adopsi Kerjasama Pemerintah dan Badan Usaha di Pemerintahan Daerah - Ida Yuliana; Rizal Z. Tamin; Iris Mahani (LPPM Universitas Abdurrab, 2025)
Public-Private Partnership (PPP) in local government is an infrastructure financing innovation introduced as a crucial solution for infrastructure procurement and improving public services in the regions. However, the adoption of the PPP scheme in various regions is considered less than optimal, where several structural obstacles hinder the potential for private investment in supporting regional development. This problem indicates the need for a deeper understanding of the factors that influence the adoption of PPP. This study aims to analyze the context of PPP adoption and develop an adoption model using the approach of three main theories: the Diffusion of Innovation Theory, Institutional Theory, and Stakeholder Theory. Through a systematic literature review of 23 publications, it was found that the majority of PPP research focuses on the post-adoption and implementation phases. More critically, all articles using a theoretical approach (Diffusion of Innovation, Institutional, and Stakeholder) were found to examine implementation at the Central Government level, and none focused on the Local Government context. This review provides in-depth insight into the drivers and barriers of PPP adoption. The implication is that these findings serve as a vital foundation for Local Governments to formulate targeted policies, thereby accelerating PPP implementation and fostering sustainable regional development.